Deriving a Template for Sustainable Forest Management in Nigeria’s Northern Guinea Savanna: Study of Detarium Microcarpum (Fabaceae) - Omijeh, Justus Eronmosele (Journal of Sustainability and Environmental Management, 2024)
Detarium microcarpum (Fabaceae) is a small tree found in the Sudan and Guinea Savanna and used for several nutritional and health purposes. A template was developed to enhance the practice of sustainable forest management. Nineteen sample trees were assessed for different growth parameters, yielding a coefficient of determination (r2) and Pearson’s correlation coefficient (r). The analysis showed the relationship between tree height and crown diameter, crown area, basal area, crown ratio, and volume as 0.22, 0.01, 0.55, 0.10, and 0.70, respectively. To assuage the harsh effects of climate change, deforestation and other anthropogenic activities should be discouraged through vigorous forest extension activities.